Frontal fibrosing alopecia: efficacy of treatment modalities - Gamret AC; Potluri VS; Krishnamurthy K; Fertig RM (Dove Medical Press, 2019)
A Caresse Gamret,1 V Sumanth Potluri,1 Karthik Krishnamurthy,2 Raymond M Fertig31Department of Dermatology and Cutaneous Surgery, University of Miami Miller School of Medicine, Miami, FL, USA; 2Division of Dermatology, Orange Park Medical Center, Orange Park, FL, USA; 3Department of Graduate Medical Education, Orange Park Medical Center, Orange Park, FL, USAAbstract: Frontal fibrosing alopecia (FFA) is a primary cicatricial alopecia characterized by loss of follicular stem cells, fibrosis, and a receding frontotemporal hairline, with frequent loss of eyebrows, and less commonly, body hair involvement. Diagnosis is clinical and the disease most often affects postmenopausal women. Treatment is difficult with the goal of disease stabilization rather than hair regrowth due to the scarring nature of FFA. To date, there are no randomized controlled trials evaluating efficacy of treatments. Therefore, much of our knowledge is based on small retrospective studies. In this review, we highlight the various and most current treatment options for FFA, including 5-α-reductase inhibitors, intralesional steroids, hydroxychloroquine, topical steroids, topical calcineurin inhibitors, systemic retinoids, pioglitazone, oral antibiotics, minoxidil, excimer laser, and hair transplantation. Currently, 5-α-reductase inhibitors, intralesional steroids, and hydroxychloroquine have the highest level of evidence for treating FFA, while the remaining therapies have variable results and require further data to draw definitive conclusions.Keywords: frontal fibrosing alopecia, frontal fibrosing alopecia treatment, FFA, FFA therapy